Local CEO and Financial Distress Risk: The Moderating Effects of Leverage - Fitriani, Nurul (Journal of Economics, Business, and Government Challenges, 2025)
This study aims to explore how having local CEOs impacts a company's likelihood of encountering financial distress, and to evaluate the role of leverage as a moderating factor in this relationship. The research employs 1,500 firm-year observations from non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, illustrating the recovery phase after COVID-19. Hierarchical regression analysis is employed to test the hypotheses, whereas the Coarsened Exact Matching (CEM) technique is employed to guarantee the reliability and stability of the findings. The results suggest that having a local CEO typically correlates with a reduced likelihood of financial distress, indicating that their emotional and social ties to the region may encourage more prudent and long-term decision-making. Nevertheless, this mitigating effect weakens in firms with higher leverage, which is independently linked to a greater risk of financial distress. The study offers a theoretical contribution by combining place attachment theory with pecking order theory to explain the dynamic between CEO locality and capital structure in shaping financial outcomes in emerging economies. It emphasizes the strategic advantage of appointing local CEOs, particularly for firms exposed to financial uncertainty. Moreover, the results underscore the importance of aligning executive characteristics with the firm’s financial profile to strengthen resilience. This research advances existing literature on local CEO impact by specifically addressing their role in mitigating financial distress and by evaluating how leverage conditions this effect.